S. DI VITA Y C. MORANDI - Mega-Events and Legacies in Post-Metropolitan Spaces. Expos and Urban Agendas - Ezquerra Alcázar, Isabel (ZARCH, 2019)
Stefano di Vita y Corinna Morandi Mega-Events and Legacies in Post-Metropolitan Spaces. Expos and Urban Agendas Michigan (USA): Palgrave Macmillan, Mega Event Planning Pivot series, 2018. 152 páginas. Idioma: inglés. DOI: 10.1007/978-3-319-67768-2